The Transcriptional Landscape of Polyploid Wheats and Their Diploid Ancestors during Embryogenesis and Grain Development. Issue 12 (18th October 2019) - Xiang, Daoquan; Quilichini, Teagen D.; Liu, Ziying; Gao, Peng; Pan, Youlian; Li, Qiang; Nilsen, Kirby T.; Venglat, Prakash; Esteban, Eddi; Pasha, Asher; Wang, Yejun; Wen, Rui; et al.
Abstract : Transcriptomic analysis of polyploid wheats and ancestral diploid grasses sheds light on the programming of embryo and grain development, gene activities, and their evolutionary implications. Abstract: Modern wheat production comes from two polyploid species, Triticum aestivum and Triticum turgidum (var durum ), which putatively arose from diploid ancestors Triticum urartu, Aegilops speltoides, and Aegilops tauschii . How gene expression during embryogenesis and grain development in wheats has been shaped by the differing contributions of diploid genomes through hybridization, polyploidization, and breeding selection is not well understood. This study describes the global landscape of gene activities during wheat embryogenesis and grain development. Using comprehensive transcriptomic analyses of two wheat cultivars and three diploid grasses, we investigated gene expression at seven stages of embryo development, two endosperm stages, and one pericarp stage. We identified transcriptional signatures and developmental similarities and differences among the five species, revealing the evolutionary divergence of gene expression programs and the contributions of A, B, and D subgenomes to grain development in polyploid wheats. The characterization of embryonic transcriptional programming in hexaploid wheat, tetraploid wheat, and diploid grass species provides insight into the landscape of gene expression in modern wheat and its ancestral species. This study presents a framework for understanding the evolution of domesticated wheat and the selective pressures placed on grain production, with important implications for future performance and yield improvements.